Is coronary computed tomography angiography a good choice for elders and high probability cases?. (25th November 2020) - Graca Santos, L; Ladeiras-Lopes, R; Ferreira, N; Faria, R; Ferreira, W; Carvalho, M; Braga, P
Abstract: Introduction: Coronary computed tomography angiography (cCTA) is widely considered the optimal non-invasive test to rule out coronary artery disease (CAD) and the gatekeeper for invasive coronary angiography (ICA). However, its diagnostic utility in elderly patients (pts) and in cases of high pre-test probability (PTP) is still questioned. Aim: To determine whether older age and high PTP are correlated with non-diagnostic cCTA scans in pts with suspected chronic coronary syndrome (CCS). Methods: Single-centre retrospective study of 302 pts with suspected CAD assigned to two groups: (A) 207 pts aged ≥70 years (y); (B) 95 aged <70y. Younger pts were randomly selected from our database. We excluded pts with known history of CAD and suspected acute coronary syndrome. A 192x2 dual-source CT equipment was used. Baseline demographic and clinical characteristics were collected as well as scan features and findings. We defined high PTP according to clinical Morise score. Our endpoint was the obtention of diagnostic scan (all segments evaluable). Multivariate analysis was performed to assess the determinants of non-diagnostic scans. We used SPSS Statistics 22 for statistical analysis. Results: Overall, mean age was 68±9y and 53% were male. Elderly pts presented more co-morbidities (hypertension: 78.3 vs 54.7%, p<0.01; hyperlipidaemia: 69.1 vs 52.6%, p<0.01; pulmonary disease: 13.0 vs 4.2%, p=0.02) and high PTP more frequently (16.9 vs 6.3%, p<0.01). Total coronary calcium score (CaS) was higher in elderly pts (382.7±658.7 vs 243.5±490.8, p=0.04); per-vessel, both left anterior descending (156.7±254.2 vs 92.2±187.8, p=0.01) and left circumflex (LCX) arteries (65.5±131.3 vs 26.8±67.6, p<0.01) showed higher CaS in the elderly. Multiple calcified plaques (≥5) were also more common in this group (60.4 vs 45.3%, p=0.01). However, the proportion of pts with CaS considered prohibitive for angiography (13.5 vs 7.4%; p=0.12) and calcium blooming artefacts impairing interpretation (14.5 vs 12.5%; p=0.65) did not differ. A diagnostic study was more frequently obtained in younger pts but without reaching statistical significance (69.1 vs 76.8%; p=0.17). Obstructive CAD was equally identified (30.3 vs 30.4%; p=0.92) with a respective per-patient accuracy of 68.4% (13/19) and 57.1% (8/14) comparing with ICA when performed. Multivariate analysis showed that LCX CaS ≥75th percentile and multiple calcified plaques (≥5) were associated with non-diagnostic cCTA scan (Figure 1). High PTP (p=0.83) and age ≥70y (p=0.61) were not associated with the endpoint. Conclusion: In this comparison study of elderly and young pts undergoing cCTA for suspected CCS, age ≥70y and high PTP were not associated with non-diagnostic tests while multiple calcified lesions and severe LCX calcification predicted inconclusive studies. Our results cast hope on the applicability of cCTA to elderly pts and cases with high PTP, although larger studies are required. Funding Acknowledgement: Type of funding source: None